Crystal structure of bis(4-(2-phenylpropan-2-yl)phenyl)amine, C30H31N - Wang Limin; Wang Shengpei; Liu Shenggao (Zeitschrift für Kristallographie - New Crystal Structures, 2016)
C30H31N, triclinic, P1̅ (no. 2), a = 8.9828(11) Å, b = 10.1648(12) Å, c = 13.2961(15) Å, α = 81.273(2)°, β = 72.201(2)°, γ = 82.271(2)°, V = 1137.5(2) Å3, Z = 2, Rgt(F) = 0.0581, wRref(F2) = 0.1545, T = 140(2) K.